2021
DOI: 10.22306/al.v8i4.229
|View full text |Cite
|
Sign up to set email alerts
|

Trade of Return Packaging in the Process of Delivery of Raw Materials on the Example of Kico-Polska Sp. Z O.O.

Abstract: An effective enterprise means correctly implemented processes. Today, logistics plays an important role in the company, and it influences the processes carried out in production companies, ensuring the implementation of its most important function - production. The article analyses the processes of trading in returnable packaging. The optimisation of these activities was carried out on the basis of a program for simulating logistics processes. The main purpose of the article is to identify the impact of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Beitzen-Heineke et al ( 2017 2021), Capistrano and Buluran (2021), Castillo and Cochran (1996), Chan (2007), Cheng and Yang (2005), Cobb (2016), Cordella et al (2008), Dang and Chu (2016), Dubiel (1996), Duhaime et al (2001), Ech-Charrat and Amechnoue (2016), Ech-Charrat et al (2017), Fan (2019), Giubilato et al (2019), Glock (2017), Goellner and Sparrow (2014), González Boubeta et al (2018), Goudenege et al (2013), Guzman et al (2021), Hekkert et al (2000a), Huang et al (2008), Hurley et al (2017), Ilic et al (2009), Itsuki (2012), Jarupan et al, 2004, Katephap andLimnararat (2015), Katephap and Limnararat (2017), Kelle and Silver (1989), Kim and Glock (2014), Koszorek and Huk (2021), Kroon and Vrijens (1995), Lampe and Strassner (2003), Legiędź and Huk (2021), Levi et al (2011), Mahmoudi and Parviziomran (2020), Maleki and Meiser (2011), Maleki and Reimche (2011), Mannur and Moreau (1992) It is vital that the pre-defined cycle-rate is satisfied to ensure the environmental benefits of adopting reusable packaging is met (Lofthouse and Bhamra, 2006;Kunamaneni et al, 2019)....…”
Section: Primary Refillable and Returnablementioning
confidence: 99%
See 2 more Smart Citations
“…Beitzen-Heineke et al ( 2017 2021), Capistrano and Buluran (2021), Castillo and Cochran (1996), Chan (2007), Cheng and Yang (2005), Cobb (2016), Cordella et al (2008), Dang and Chu (2016), Dubiel (1996), Duhaime et al (2001), Ech-Charrat and Amechnoue (2016), Ech-Charrat et al (2017), Fan (2019), Giubilato et al (2019), Glock (2017), Goellner and Sparrow (2014), González Boubeta et al (2018), Goudenege et al (2013), Guzman et al (2021), Hekkert et al (2000a), Huang et al (2008), Hurley et al (2017), Ilic et al (2009), Itsuki (2012), Jarupan et al, 2004, Katephap andLimnararat (2015), Katephap and Limnararat (2017), Kelle and Silver (1989), Kim and Glock (2014), Koszorek and Huk (2021), Kroon and Vrijens (1995), Lampe and Strassner (2003), Legiędź and Huk (2021), Levi et al (2011), Mahmoudi and Parviziomran (2020), Maleki and Meiser (2011), Maleki and Reimche (2011), Mannur and Moreau (1992) It is vital that the pre-defined cycle-rate is satisfied to ensure the environmental benefits of adopting reusable packaging is met (Lofthouse and Bhamra, 2006;Kunamaneni et al, 2019)....…”
Section: Primary Refillable and Returnablementioning
confidence: 99%
“…It is widely accepted that closed loop systems are more labour intensive through collection, cleaning and transportation (Castillo and Cochran, 1196). It is also noted that reusable packaging can be large and unwieldy making it difficult to manage at some stages on the supply chain (Legiędź and Huk, 2021). There is a trade-off between increased volume and the increased handling time, however in a study by McGlynn et al (2003a, b) reusable packaging has been shown to hold 4 times more food and increase process time by only 1.4 to 2 times as long.…”
Section: Economic Factorsmentioning
confidence: 99%
See 1 more Smart Citation